Effective coverage for antiretroviral therapy in a Ugandan district with a decentralized model of care - Scheibe, Florian; Waiswa, Peter; Kadobera, Daniel; Müller, Olaf; Ekström, Anna M.; Sarker, Malabika; Neuhann, Florian (PLOS ONE, 2013)
Introduction While increasing access to antiretroviral therapy (ART) is reported from many African countries, data on effective coverage particular from settings without external support or research remains scarce. We examined and report effective coverage data from a public ART program in rural Uganda. Methods We conducted a retrospective cohort study at all ART-providing governmental health facilities in Iganga District, Eastern Uganda. Based on all HIV patients registered between April 2004 and September 2009 (n = 4775), we assessed indicators of program performance and determined rates of retention and Cox proportional hazards for attrition. Effective ART coverage was calculated using projections (SPECTRUM software) adapted to the district demographic structure and number of people receiving ART. Results By September 2009, district public sector effective ART coverage was 10.3% for adults and 1.9% for children. After a median follow-up of 26.9 months, overall ART retention was 54.7%. The probability of retention was 0.72 (95% confidence interval (CI) 0.69-0.75) at 12 and 0.58 (CI 0.54-0.62) at 36 months after ART initiation. Individual health facilities differed considerably regarding performance indicators and retention. Overall, 198 (16.9%) individual files of 1171 registered ART patients were lost. Young adult age (15-24 years) had a higher risk of attrition (HR 2.1, CI 1.4-3.2) as well as WHO stage I (HR 4.8, CI 1.9-11.8) and WHO stage IV (HR 2.5, CI 1.3-4.7). An interval ≥6 weeks between HIV testing and ART initiation was associated with a reduced risk (HR 0.6, CI 0.47-0.78). Conclusion Compared to reported national data effective ART coverage in Iganga District was low. Intensified efforts to improve access, retention in care, and quality of documentation are urgently needed. Children and young adults require special attention in the program.